METHODICAL ASPECTS OF SYSTEM MAXIMA IN LEARNING PROCESS OF OPERATIONS RESEARCH - Kobylnyk, Т.П.; Kohut, У.П. (Journal of Information Technologies in Education (ITE), 2016)
Training of operations research of bachelors of Computer Science is particularly important because combines both fundamental concepts and principles of mathematics and informational different disciplines and applied models and algorithms for their use. One of the urgent problems of higher education is creation of a methodological training systems targeted at a broad, yet educationally balanced use of modern learning process and information and communication technologies, including computer systems of mathematics. It is scientifically based, educationally balanced and appropriate implementation of these tools in the educational institutions will increase the level of information technological support and substantial growth of informational and fundamental mathematical training of future specialists in computer science. Because of this, there is need to identify ways of using ICT in learning process of operations research of Bachelor of Computer Science in Pedagogical Universities, modernizing the learning environment, taking into account trends in the development of science and technology, improving teaching training systems, including through the use of computer mathematics system as learning tools. This article analyzes the experimental study of effectiveness of using the system Maxima methods in learning of operations research of bachelors of computer science. The article outlines the pedagogical directions of use of computer mathematics system (CMS) at studying operations research; highlights the methodological aspects of CMS Maxima in the study of this course. The purpose of the article is an experimental trial of CMS Maxima as a means of teaching of operations research of bachelors of computer science. The object of investigation is the learning process of bachelors of computer science with the use of CMS. The subject of investigation is the peculiarities of CMS Maxima using as a learning tool of support for computer science courses.